2016
DOI: 10.1186/s40608-016-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the receipt of influenza and pneumococcal vaccination: a systematic review and meta-analysis

Abstract: BackgroundObesity is a risk factor for inadequate receipt of recommended preventive care services. The objective of this study was to assess the relationship between increasing body mass index and receipt of influenza and pneumococcal vaccinations. A systematic review of the PubMed, Embase, and Web of Science databases was conducted from January 1966 to May 2015 for cohort and cross-sectional studies that assessed the relationship between body mass index and the receipt of vaccinations for influenza and pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
10
1
1
Order By: Relevance
“…Despite risks for complications from COVID‐19 associated with obesity (1,14), individuals with higher BMI were no more concerned about the pandemic than individuals with normal weight. Furthermore, although previous research has found fairly consistent evidence that individuals with obesity are more likely to engage in some preventive behaviors, such as flu vaccinations (15), participants with higher BMI were no more or less likely than individuals with lower BMI to engage in behaviors to protect themselves and others against the coronavirus. Given the risks of complications from COVID‐19, precautionary behaviors may be especially important for individuals with higher BMI.…”
Section: Discussionmentioning
confidence: 84%
“…Despite risks for complications from COVID‐19 associated with obesity (1,14), individuals with higher BMI were no more concerned about the pandemic than individuals with normal weight. Furthermore, although previous research has found fairly consistent evidence that individuals with obesity are more likely to engage in some preventive behaviors, such as flu vaccinations (15), participants with higher BMI were no more or less likely than individuals with lower BMI to engage in behaviors to protect themselves and others against the coronavirus. Given the risks of complications from COVID‐19, precautionary behaviors may be especially important for individuals with higher BMI.…”
Section: Discussionmentioning
confidence: 84%
“…In the current study, the univariate analysis showed that influenza coverage was higher in overweight and obese older people than in those with a normal weight. According to a recent systematic review and meta-analysis, people with obesity may be both more likely to perceive higher risk from vaccine-preventable diseases and more accepting of the benefits and safety of recommended vaccinations [68]. On the other hand, the results of this study are in line with other studies [51,[69][70][71], which show that poor self-perceived health status is associated with receiving vaccinations, while a good self-perceived health status is the most common reason for the refusal to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…One large study identified disrespectful treatment, embarrassment with being weighed, negative attitudes of providers, unsolicited weight loss advice, and poorly fit equipment and facilities as reasons why women with obesity were more likely to delay screening for breast and cervical cancer (Amy, Aalborg, Lyons, & Keranen, 2006). Previous studies have noted mixed findings when assessing disparities by body weight in receipt of HPV, pneumococcus, or influenza vaccinations, but no HPV vaccination studies have included adolescent and adult women in a large, nationally representative sample or controlled for known confounders such as differences in healthcare utilization (Harper et al, 2014; Harris, Moniz, Iott, Power, & Griggs, 2016; Sundaram, Mason, & Basta, 2016).…”
Section: Introductionmentioning
confidence: 99%